ANALISIS MANAJEMEN PERSEDIAAN PADA CV FOKUS USAHA - Aprilia Tangkelayuk; Daniel Nemba Dambe (JURNAL ULET (Utility, Earning and Tax), 2020)
This study aims to determine the optimal number of orders each time and the point of reordering Semen Tonasa 50 kg and Zinc 0.20 mm which should be done by CV Fokus Usaha. The method used is descriptive. The analytical instrument used is the Economic Order Quantity (EOQ) and Reorder Point (ROP) analysis. The results showed that: (1) The optimal order quantity for Semen Tonasa 50 kg is 428 sacks and for Zinc 0.20 mm is 8,311 pieces. (2) The reorder point can be made when the supply of Semen Tonasa 50 kg remains 70 sacks and Zinc 0.20 mm remains 2,805 pieces